Academic stress in university students in the face of virtual education associated with covid-19 - Luque-Vilca, Olivia Magaly (2022)
Academic stress in university students associated with the COVID-19 pandemic is increasing due to the change from face-to-face to virtual education, causing decreased motivation and increased anxiety in students. The aim of this study is to evaluate academic stress in university students in the face of virtual education associated with COVID-19. To this end, the validated academic stress questionnaire SISCO SV- COVID-19 was applied, and 92.27% of the students surveyed had academic stress, identifying the overload of tasks and work to be completed within the deadlines set by teachers as a stress factor.